The Efficacy of Mycophenolate Mofetil in Remission Maintenance Therapy for Microscopic Polyangiitis and Granulomatosis with Polyangiitis - Pyo, Jung Yoon; Lee, Lucy Eunju; Ahn, Sung Soo; Song, Jason Jungsik; Park, Yong-Beom; Lee, Sang-Won (Yonsei medical journal, 2021)
The present study compared the efficacy of mycophenolate mofetil (MMF) with that of azathioprine (AZA) in Korean patients with microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA). The medical records of 69 patients with MPA and GPA who received cyclophosphamide and subsequently received AZA or MMF for remission maintenance therapy were reviewed. All-cause mortality, relapse, end-stage renal disease (ESRD), cerebrovascular accident, and cardiovascular disease were evaluated as poor outcomes. Having a lower Birmingham Vasculitis Activity Score (BVAS) was defined as the lowest tertile of BVAS (BVAS ≤11 in this study). In comparative analysis of the occurrence of poor outcomes among patients taking AZA only, MMF only, and MMF after AZA, patients taking MMF only exhibited a significantly lower cumulative ESRD-free survival rate than patients taking AZA only ( =0.028). In terms of ESRD occurrence between the groups based on BVAS at diagnosis, among patients with MPA and GPA with higher BVAS at diagnosis, patients taking MMF only exhibited a significantly lower cumulative ESRD-free survival rate than those taking AZA only ( =0.047). Among patients with MPA and GPA with the lowest tertile of BVAS at diagnosis, cumulative ESRD-free survival rates did not differ. With regard to ESRD occurrence, the efficacy of MMF in remission maintenance therapy was less effective than AZA in patients with MPA and GPA. However, among patients with lower BVAS, there was no difference in the occurrence of poor outcomes between patients taking MMF and those taking AZA.